Processos mediativos e formação de conceitos cotidianos: implicações nas dificuldades de aprendizagem - Cenci, Adriane (2011)
The research integrates the Field of Research of Special Education of the Program of Post Graduation in Education of UFSM. The issues which initiated the research are derived from the work developed with two boys (univiteline twins) that present learning disabilities. The main objective of the research was to understand how the mediating processes influence the formation of everyday concepts, more specifically mathematical everyday concepts, and how the latter interfere in the formation of scientific concepts and in school learning, wich can trigger learning disabilities. Thus, looking for methodological support in the principles of Qualitative Epistemology of González Rey and in the Vygotskian premises which point to the inseparability between theory and method, a work was developed along with the two boys with pedagogical assistance and following up in class during a semester. The actions in the field were being defined according to the advance of the interpretations in the light of empirical observations and with the progress of the theoretical studies. The indicators that had been appearing along the investigation headed to three nucleus or areas of meaning which gave intelligibility to the case, that is, it allows to perceive/interpret/comprehend the case. The first nucleus of meaning centers in the relation between everyday concepts and scientific concepts and ratifies the interrelation Vygotsky proposed that existed between both. Proceeding, in the second area of meaning it was perceived the issue of mediation as central in the process of formation of concepts, attesting that the shortage of experiences of mediated learning brought on the incipient development of everyday concepts in both children as basis for the nucleus we have also looked for references in the work of Reuven Feuerstein. The third area of meaning invokes again the referential of González Rey and indicates the importance of the study of subjectivity, since learning involves more than cognition, it involves aspects related to emotions, expectations, and to the motivation of learning such aspects are in the constitution of learning disabilities in the subjects of research. We believe that the contributions of research for the area (field) of Education and Special Education come in the amplification of interpretation regarding the formation of concepts in Vygotsky. In the investigated case, it was verified that the absence of mediated learning experiences and also that subjective meanings allied to the low expectation of school success are factors that influence the formation of everyday concepts and consequently interfere in the formation of scientific concepts and in school learning, setting off learning disabilities.